The absence of centrioles from spindle poles of rat kangaroo (PtK2) cells undergoing meiotic-like reduction division in vitro (The Rockefeller University Press, 1977)
Light and electron microscopy were used to study somatic cell reduction division occurring spontaneously in tetraploid populations of rat kangaroo Potorous tridactylis (PtK2) cells in vitro. Light microscopy coupled with time-lapse photography documented the pattern of reduction division which includes an anaphase-like movement of double chromatid chromosomes to opposite spindle poles followed by the organization of two separate metaphase plates and synchronous anaphase division to form four poles and four daughter nuclei. The resulting daughter cells were isolated and cloned, showing their viability, and karyotyped to determine their ploidy. Ultrastructural analysis of cells undergoing reduction consistently revealed two duplexes of centrioles (one at each of two spindle poles) and two spindle poles in each cell that lacked centrioles but with microtubules terminating in a pericentriolar-like cloud of material. These results suggest that the centriole is not essential for spindle pole formation and division and implicate the could region as a necessary component of the spindle apparatus.